Centralized Consensus Hemagglutinin Genes Induce Protective Immunity against H1, H3 and H5 Influenza Viruses - Webby, Richard J. (PLoS One, 2015)
With the exception of the live attenuated influenza vaccine there have been no substantial changes in influenza vaccine strategies since the 1940’s. Here we report an alternative vaccine approach that uses Adenovirus-vectored centralized hemagglutinin (HA) genes as vaccine antigens. Consensus H1-Con, H3-Con and H5-Con HA genes were computationally derived. Mice were immunized with Ad vaccines expressing the centralized genes individually. Groups of mice were vaccinated with 1 X 10(10), 5 X 10(7) and 1 X 10(7) virus particles per mouse to represent high, intermediate and low doses, respectively. 100% of the mice that were vaccinated with the high dose vaccine were protected from heterologous lethal challenges within each subtype. In addition to 100% survival, there were no signs of weight loss and disease in 7 out of 8 groups of high dose vaccinated mice. Lower doses of vaccine showed a reduction of protection in a dose-dependent manner. However, even the lowest dose of vaccine provided significant levels of protection against the divergent influenza strains, especially considering the stringency of the challenge virus. In addition, we found that all doses of H5-Con vaccine were capable of providing complete protection against mortality when challenged with lethal doses of all 3 H5N1 influenza strains. This data demonstrates that centralized H1-Con, H3-Con and H5-Con genes can be effectively used to completely protect mice against many diverse strains of influenza. Therefore, we believe that these Ad-vectored centralized genes could be easily translated into new human vaccines.